Linear stability effect of densely distributed porous medium and Coriolis force on Soret driven ferrothermohaline convection - Sekar, R.; Murugan, D. (Zielona Góra: Uniwersytet Zielonogórski)
The effect of Coriolis force on the Soret driven ferrothermohaline convection in a densely packed porous medium has been studied. A linear stability analysis is carried out using normal mode technique. It is found that stationary convection is favorable for the Darcy model, therefore oscillatory instability is studied. A small thermal perturbation is applied to the basic state and linear stability analysis is used for which the normal mode technique is applied.
Keywords: Coriolis force; Darcy model; Soret effect; ferrofluid; thermohaline convection